Effect of Pranayama on Orientation Ability of Cricketers of JECRC University Jaipur - Mr. Mahendra Kumar Jangir; Dr. Abhishek Sanchora (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The objective of present study was to find out effect of the eight weeks training programme of Pranayama on the Orientation Ability of male cricketers of JECRC University. For the purpose of study, 80 male Cricketers from the JECRC University, Jaipur was randomly selected as subjects for this study. The subject age was ranged between 17 to 24 years. 40 subjects were selected for each group i.e. one experimental groups and one control group. All subjects were, randomly divided into one experimental groups and one control group. The groups ‘A’ was experimental groups and received training program. The group B served as a control group and continued participating in the normal program. Pranayama were considered as independent variable. Orientation was selected as dependent variable. Findings revealed that “t” values (8.88) of comparison between treatment pre group and treatment post group in relation to Orientation Ability was found to be significant at 0.05 level. On basis of findings it is concluded that significant effect of eight weeks training program of Pranayama on Orientation Ability of cricketers of JECRC University.